Real-world cryptography (Manning Publications, 2021)
In Video Editions the narrator reads the book while the content, figures, code listings, diagrams, and text appear on the screen. Like an audiobook that you can also watch as a video. A staggeringly comprehensive review of the state of modern cryptography. Essential for anyone getting up to speed in information security. Thomas Doylend, Green Rocket Security An all-practical guide to the cryptography behind common tools and protocols that will help you make excellent security choices for your systems and applications. In Real-World Cryptography you will find: Best practices for using cryptography Diagrams and explanations of cryptographic algorithms Implementing digital signatures and zero-knowledge proofs Specialized hardware for attacks and highly adversarial environments Identifying and fixing bad practices Choosing the right cryptographic tool for any problem Real-World Cryptography reveals the cryptographic techniques that drive the security of web APIs, registering and logging in users, and even the blockchain. You'll learn how these techniques power modern security, and how to apply them to your own projects. Alongside modern methods, the book also anticipates the future of cryptography, diving into emerging and cutting-edge advances such as cryptocurrencies, and post-quantum cryptography. All techniques are fully illustrated with diagrams and examples so you can easily see how to put them into practice. about the technology Cryptography is the essential foundation of IT security. To stay ahead of the bad actors attacking your systems, you need to understand the tools, frameworks, and protocols that protect your networks and applications. This book introduces authentication, encryption, signatures, secret-keeping, and other cryptography concepts in plain language and beautiful illustrations. about the book Real-World Cryptography teaches practical techniques for day-to-day work as a developer, sysadmin, or security practitioner. There's no complex math or jargon: Modern cryptography methods are explored through clever graphics and real-world use cases. You'll learn building blocks like hash functions and signatures; cryptographic protocols like HTTPS and secure messaging; and cutting-edge advances like post-quantum cryptography and cryptocurrencies. This book is a joy to listen to--and it might just save your bacon the next time you're targeted by an adversary after your data. about the audience For cryptography beginners with no previous experience in the field. about the author David Wong is a cryptography engineer. He is an active contributor to internet standards including Transport Layer Security. Covers all the important parts of applied cryptography. A must-read for every Java developer. Harald Kuhn, TurnFriendly An in-depth introduction to cryptography, covering hot topics like blockchain and quantum computing. Gábor László Hajba, ProLion A best-in-category book that takes you all the way from curious novice to confident practitioner. William Rudenmalm, Creandum NARRATED BY DEREK DYSART.